The contribution of transdiagnostic vulnerability factors in patients with chronic insomnia - Habibi Asgarabad, Mojtaba; Doos Ali Vand, Hoda; Salehi Yegaei, Pardis; Hooman, Farzaneh; Ahmadi, Reza; Baglioni, Chiara; Moradi, Shahram (Frontiers in Psychiatry, 2023)
Introduction Various transdiagnostic factors have been associated with insomnia severity. The current study aimed to predict insomnia severity based on a group of transdiagnostic factors including neuroticism, emotion regulation, perfectionism, psychological inflexibility, anxiety sensitivity, and repetitive negative thinking after controlling for depression/anxiety symptoms and demographic characteristics. Methods Two hundred patients with chronic insomnia disorder were recruited from a sleep disorder clinic. Participants completed the Insomnia Severity Index (ISI), Clinical Perfectionism Questionnaire (CPQ), Acceptance and Action Questionnaire-II (AAQ-II), Anxiety Sensitivity Index-3 (ASI-3), Repetitive Thinking Questionnaire (RTQ-10), Big Five Inventory (BFI-10), Emotion Regulation Questionnaire (ERQ), and Depression Anxiety Stress Scale (DASS-21). Results After controlling for the confounding variables (depression/anxiety symptoms and demographic characteristics), hierarchical multiple linear regression suggested the significant association of neuroticism (BFI), cognitive reappraisal (ERQ), personal standards (CPQ), evaluative concerns (CPQ), physical concerns (ASI), cognitive concerns (ASI), and repetitive negative thinking (RTQ) with insomnia severity. Discussion The findings support the role of transdiagnostic factors, especially physical concerns, repetitive negative thinking, and neuroticism in chronic insomnia. Future research using longitudinal designs is required to verify the causal status of transdiagnostic variables.